THE ROLE OF THE ANTI CORRUPTION COMMISSION (CAC) IN DRIVING BUREAUCRATIC REFORM TOWARDS GOOD GOVERNANCE IN TIMOR LESTE - Jaimito Soares, Patricia Baliana da Costa, Carolina da Cruz Simeão Fatima Martins, Domingos Loe Soar (JURNAL PENDIDIKAN IPS, 2026)
Corruption is a primary obstacle to development and bureaucratic reform in post-conflict nations like Timor-Leste, where state institutions are still consolidating. In an environment characterized by a weak rule of law and strong patronage networks inherited from its period of struggle for independence, corruption not only harms state finances but also erodes government legitimacy and hinders human resource development. This study aims to critically and comprehensively analyze the role of the Anti-Corruption Commission (Comissão Anti-Corrupção/CAC) in promoting bureaucratic reform towards good governance in Timor-Leste. Utilizing a qualitative research method with a case study approach, data were collected through a comprehensive analysis of documents, including CAC annual reports, statistical data from the World Bank and Transparency International, national legal frameworks, and relevant literature. The findings indicate that the CAC plays a crucial and multifaceted role through its "Trisula Strategy": enforcement to create a deterrent effect and uphold the law, prevention as a catalyst for systemic reform, and education as the foundation for building a culture of integrity. Despite facing significant challenges such as resource limitations, uneven technical capacity, and alleged political interventions that test its independence, the CAC's enforcement actions in several high-profile cases have successfully elevated the discourse on public sector accountability. Concurrently, its systemic prevention and education programs, implemented gradually, have contributed to increased awareness and a paradigm shift in the bureaucratic culture, although implementation is often hampered by internal resistance. The CAC's effectiveness has not yet reached an optimal level and is highly dependent on strong political commitment from the governing elite and broader institutional reforms. This study recommends strengthening the CAC's institutional independence legally and financially, increasing results-oriented budget allocations, and fostering closer, more structured synergy with the judiciary, parliament, and civil society to accelerate the realization of sustainable good governance in Timor-Leste.